Sectorized fallow agriculture in the heights of Paucartambo: Struggles over the ecology of productive space during the 16th and 20th centuries - Zimmerer, Karl S. (1991)
Throughout much of the Central Andes, between southern Bolivia and central Peru, land use in the higher agricultural areas is organized in a different form of production known as the sectorized fallow system. Called by a variety of names in the different regions of the Central Andes (suyu, aynoqa, mañay, laymi, manda, luck, shifts, which are reviewed in Mayer 1979 and Orlove and Godoy 1986), the sectorized fallow system involves the socially coordinated rotation of cropland and grazing land among a series of large areas known as sectors.